KEPEMIMPINAN TRANSFORMASIONAL ISLAMI DALAM PENGEMBANGAN TEACHING FACTORY DI SMK - Widianti, Windi; Bedi, Fisman; Fitri, Tin Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The implementation of teaching factories in Vocational High Schools (SMKN) in Indonesia is a strategic approach to prepare students for industry demands. However, in the context of Islamic-based education, the teaching factory aims not only to enhance technical skills but also to integrate Islamic values to shape student character. This study aims to explore the role of transformational leadership of school principals in the development of Islamic-based teaching factories in the mechanical engineering departments of SMKN. Using a literature review method, this study analyzes various academic sources related to transformational leadership, teaching factories, and the integration of Islamic values in vocational education. The results show that the transformational leadership of school principals based on Islamic values significantly contributes to building an ethical, collaborative school culture that promotes the Islamic character of students. The integration of Islamic values in the teaching factory creates a balance between technical skills and morality and establishes connections with ethically oriented industries. This study contributes new insights by emphasizing the importance of Islamic-based leadership in vocational education, which builds not only technical competencies but also character.